2023
DOI: 10.1037/ppm0000415
|View full text |Cite
|
Sign up to set email alerts
|

Facebook, Twitter, and Instagram: Simultaneously examining the association between three social networking sites and relationship stress and satisfaction.

Abstract: With the evolving normalcy of sharing personal information online and utilizing communication technology as a means to talk to other users, more research is required concerning the impact of social media, or social networking sites (SNSs), on romantic relationship health and stability. This study uses the systemictransactional model of dyadic coping to assess the association between Facebook, Twitter, and Instagram usage with romantic relationship stress and romantic relationship satisfaction. Two hundred and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…For example, Halpern et al (2017) found that jealousy indirectly predicted poorer romantic relationship quality through social media photo-related conflicts. Delle et al (2022) found that active use of Twitter and Instagram was negatively associated with relationship satisfaction through romantic relationship stress among adults aged 18–46. Few have studied the impact of jealousy on friendship quality (exception Parker et al, 2016 ).…”
Section: Studymentioning
confidence: 96%
“…For example, Halpern et al (2017) found that jealousy indirectly predicted poorer romantic relationship quality through social media photo-related conflicts. Delle et al (2022) found that active use of Twitter and Instagram was negatively associated with relationship satisfaction through romantic relationship stress among adults aged 18–46. Few have studied the impact of jealousy on friendship quality (exception Parker et al, 2016 ).…”
Section: Studymentioning
confidence: 96%
“…12 Twitter is among the most influential social media platforms, with ≈145 million daily users and 330 million monthly users. 13 Although Twitter can be a source of reliable health information, health‐related misinformation and disinformation are highly prevalent. 14 , 15 …”
mentioning
confidence: 99%